Production and biochemical characterization of Pleurotus ostreatus NRC 620 laccase and evaluation of its efficacy in apple juice clarification - Ali M. Elshafei; Maysa A. Elsayed; Gamil E. Ibrahim; Nayra S. Mehanna; Mohamed M. Hassan; Abdelmageed M. Othman (Scientific Reports)
Abstract The highest activity of the Pleurotus ostreatus NRC620 laccase enzyme occurred in the broth of mushroom growth after 25 days of incubation at 28 °C and static conditions. The optimum pH and temperature of the enzyme activity were revealed at pH 3.0, and 70 °C, respectively, and retained 68.33 and 59.61% of its activity after incubation at 40 and 50 °C for 2 h, respectively. The enzyme retained 100% activity after 2 h of incubation in citrate–phosphate buffer (pH 7.0). The addition of MgSO4 and CuSO4 with concentrations of 10 mM caused about 21% and 35% increase in enzyme activity, while NaCl, MnCl2, KCl, and CaCl2 inhibited the enzyme. The values of the kinetic parameters (K m and V max ) of the Pleurotus ostreatus NRC 620 laccase were 1.99 mM and 16,217 µmol Min−1 L−1 respectively, using ABTS as a substrate. The apple juice enzyme-treated sample showed a significant reduction in pH, as well as viscosity, after enzyme treatment along with storage time. Apple juice treatment with laccase exhibited slight degradation in total phenolic; however, this observation was not found in antioxidant activity.